Toxicity and translocation of Ag, CuO, ZnO and TiO2 nanoparticles upon exposure to fish intestinal epithelial cells. Issue 8 (29th June 2021) - Geppert, Mark; Sigg, Laura; Schirmer, Kristin
Abstract : Understanding the ability of fish intestinal cells to act as a barrier for nanoparticle (NP) uptake and their effects is of significance from an environmental perspective as well as for human health, for which fish serves as an important nutrient source. Abstract : Understanding the ability of fish intestinal cells to act as a barrier for nanoparticle (NP) uptake and their effects is of significance from an environmental perspective as well as for human health, for which fish serves as an important nutrient source. We used an in vitro intestinal barrier model, based on rainbow trout intestinal (RTgutGC) cells, to elaborate the toxicity and translocation of five types of metal-based NPs. The NPs were polyvinylpyrrolidone (PVP)-coated Ag NPs, uncoated Ag NPs, CuO NPs, ZnO NPs and TiO2 NPs. In conventional monolayers on impermeable supports, cell viability declined according to classical sigmoidal dose–response curves with EC50 values between 0.28 mg L −1 and >100 mg L −1 in the following rank order, from the most toxic (lowest EC50) to the least toxic (highest EC50): PVP–Ag NPs < uncoated Ag NPs < CuO NPs < ZnO NPs < TiO2 NPs. When cells were cultured on permeable membranes to mimic an intestinal lumen and a blood-facing side, however, a much higher resistance of the cells towards NP-induced stress was noted with little to no impact on cell viability or barrier integrity. Yet, increased levels of Ag, Cu and Zn but not Ti were measured in the blood-side mimicking (basolateral) compartment, indicating translocation of Ag, Cu, and Zn-based NPs or ions liberated from them through the epithelial cell layer. Since especially CuO NPs appeared to be translocated as intact particles, they were investigated in more detail. A time- and temperature-dependent analysis, involving different endocytosis inhibitors, suggested that CuO NPs were translocated through the epithelium by apical caveolae-mediated endocytosis followed by delayed export onto the basolateral side. These data give valuable insights into NP uptake by, and translocation through, the fish intestinal epithelium and will be of value for future research on the molecular mechanisms of NPs that enter the fish via this critical uptake route.